Bronze age Northern Eurasian genetics in the context of development of metallurgy and Siberian ancestry - Childebayeva, Ainash; Fricke, Fabian; Rohrlach, Adam Benjamin; Huang, Lei; Schiffels, Stephan; Vesakoski, Outi; Mannermaa, Kristiina; Semerau, Lena; Aron, Franziska; Solodovnikov, Konstantin; Rykun, Marina; Moiseyev, Vyacheslav; et al. (Springer Nature, 2025)
The Eurasian Bronze Age (BA) has been described as a period of substantial human migrations, the emergence of pastoralism, horse domestication, and development of metallurgy. This study focuses on two north Eurasian sites sharing Siberian genetic ancestry. One of the sites, Rostovka, is associated with the Seima-Turbino (ST) phenomenon (~2200-1900 BCE) that is characterized by elaborate metallurgical objects found throughout Northern Eurasia. The genetic profiles of Rostovka individuals vary widely along the forest-tundra Siberian genetic cline represented by many modern Uralic-speaking populations, and the genetic heterogeneity observed is consistent with the current understanding of the ST being a transcultural phenomenon. Individuals from the second site, Bolshoy Oleni Ostrov in Kola, in comparison form a tighter cluster on the Siberian ancestry cline. We further explore this Siberian ancestry profile and assess the role of the ST phenomenon and other contemporaneous BA cultures in the spread of Uralic languages and Siberian ancestry.